Strategi Komunikasi Pemasaran PT. Mitra Property Group Dalam Meningkatkan Penjualan Property Di Perumahan Sentul City Bogor - Azizah Des Derivanti; Aulia Ramadhani (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research aims to analyze marketing communication strategies used by PT. Property Group Partners to increase property sales in Sentul City Bogor residential complex. The research uses a qualitative approach, by collecting data through in-depth interviews and observations of PT marketing team. Property Group Partners. Data analysis shows that PT. Property Group partners implement a wide range of effective marketing communication strategies, including social media use, property exhibitions and promotional activities. Social media such as Instagram, WhatsApp, Facebook, TikTok, and YouTube have become very popular and effective communication channels in reaching a broad target audience. Using social media, companies can generate interesting content, inform the advantages of properties offered, and interact directly with potential buyers. In addition, advertising media platforms such as Rumah123, Rumah.com, Lamudi, and Olx also have an important role in property promotion. PT. Property Group partners actively participate in property exhibitions at Sentul City Bogor and property events outside the region to expand their marketing reach. In addition, promotional activities such as price discounts, installment payment programs, and attractive incentives are also applied to attract potential buyers. Effective communication between marketing teams and prospective buyers is also an important factor in increasing property sales. Marketing Communication Strategy used by PT. Property Group partners have successfully increased property sales in Sentul City Bogor.